PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK ELEKTRONIK GEOGEBRA PADA MATERI REFLEKSI DAN TRANSLASI SMP - Angelin Ica Pramesti; Niluh Sulistyani (Program Studi PGSD Universitas Flores, 2024)
GeoGebra E-LKPD can helps students in visualizing and also understanding concepts on Reflection and Translation SMP. This study aims to determine the development process of GeoGebra E-LKPD on geometry transformation material and determine the validity of the E-LKPD. The method used in this research is Research and Development (R&D) with a 4-D development model with four stages, namely define includes analysis of initial abilities, tasks, and objectives; the design stage includes media selection, determining the presentation format, and making preliminary product designs; the develop stage includes validity testing, product trials, and product revisions; and the desseminate stage is product dissemination. The subjects in this study were students of class IX A of SMP Kanisius Gayam. Data were collected through interviews, observations, and expert validation sheets. In the research process also involved 2 experts who graduated from S2 mathematics education as validators. The result of this research is a valid E-LKPD with a percentage value of 84% and 89.3% with an average percentage of 86.65% so it can be concluded that this E-LKPD is suitable for use.